Estimation of river flow properties using Arc-GIS, HEC-GEO-RAS, HEC-RAS, and gauge data in Northwest, Pakistan - Nazir, Jabir; Ali, Muhammad (The Nucleus, 2026)
The accurate estimation of river discharge properties is challenging because of the lack of gauge data in inaccessible and remote regions, uneven distribution of gauge networks, and data-sharing complexities. To address these challenges, innovative integrated techniques must be evaluated. This study aimed to integrate geospatial (HEC-GEORAS), HEC-RAS, and river gauge data to quantify river flow properties, including the discharge rate, velocity, water level, and flow depth of a distributary of the Indus River in northwestern Pakistan. The study area is characterized by semi-arid conditions, experiencing water scarcity, and declining water levels. Such an integrated approach has never been used in the region, especially on any distributary of the Indus River, until now. The findings revealed that the peak flow velocity reached 1.8 m/s, and the spatial distribution varied from 0.3 to 1.3 m/s. The maximum depth was estimated at approximately 33 m in the upstream section and showed a declining trend of a few centimeters in the downstream section. River discharge decreases downstream (from 2.26 to 0.28 m3/s) due to infiltration, tributary water distribution, evaporation, and agricultural water use. The estimation of hydraulic parameters provides meaningful information for sustainable water resource management, such as domestic, agricultural, and industrial water allocations. Furthermore, the results can support flood risk assessment, irrigation planning, and adaptation to climate change strategies by improving our understanding of water availability and flow dynamics in semi-arid river systems.